Ancestral origin of variation in the triosephosphate isomerase gene promoter - Humphries, A.; Ationu, A.; Lalloz, Michel R. A.; Layton, D. M. (Human genetics, 1999)
A high frequency of nucleotide substitutions -5A/G, -8G/A, -24T/G in the triosephosphate isomerase (TPI) gene promoter has been demonstrated in African-Americans. The biological significance of these promoter variants, two of which, -8G/A and -24T/G, occur within regulatory elements essential for transcription, is controversial. The geographical distribution and frequency of allelic variation in the TPI promoter was determined in 378 unrelated normal subjects from sub-Saharan African (n = 103), Caribbean (n = 26), Northern European (n = 57), Mediterranean (n = 55), Middle Eastern (n = 42), Asian Indian (n = 48) and Oriental (n = 47) populations. Five haplotypes were identified: the common haplotype, -5A-8G-24T, -5G, -8A, -5G-8A, and -5G-8A-24G. All, with the exception of the -8A haplotype, were present in geographically dispersed populations. The -5G allele, which was found at varying frequency in all groups, has attained high frequency in the African, Caribbean and Oriental populations. Phylogenetic comparison suggests this may represent the ancestral promoter haplotype. Homozygosity for the -5G-8A haplotype identified in four subjects confirms that these variants are not responsible for a null allele as formerly postulated. Linkage disequilibrium between related TPI promoter haplotypes, -5G, -5G-8A and -5G-8A-24G, and a single nucleotide polymorphism at nt2262 of the TPI gene supports a single ancestral origin for these mutations which precedes the separation of African and non-African populations.